Orthogonal array designs for the optimization of liquid-liquid-liquid microextraction of nonsteroidal anti-inflammatory drugs combined with high-performance liquid chromatography-ultraviolet detection - Wu, J. (2014)
10.1016/j.chroma.2005.07.032